Boredom, Cyberloafing, Fairness, and Generation Y (Millennial) Performance in Indonesia’s Logistics Sector: The Mediating Role of Organizational Commitment - Turnip, Dedianto; Usman, Bahtiar; Aseanty, Deasy; Silalahi, Andri Dayarana K. (Ilomata International Journal of Management, 2026)
Introduction: This study examines whether job boredom, cyberloafing, and perceived organizational justice are associated with in-role performance among Generation Y (Millennial) employees in Indonesia’s logistics sector and whether organizational commitment mediates these relationships. Novelty: Prior Indonesian logistics studies have largely focused on younger cohorts and have rarely tested boredom, cyberloafing, and fairness simultaneously. This study tests the commitment-based mediation mechanism in a large multi-firm sample and evaluates competing interpretations of cyberloafing (withdrawal vs. short recovery). Methods: A cross-sectional survey was administered at the end of 2024 to non-managerial Generation Y employees (born 1981–1996) in eight logistics companies in Jakarta (n = 623). Measures used 5-point scales. Structural equation modeling (AMOS 23) was used to test direct and indirect effects. Results: Job boredom was negatively associated with organizational commitment and performance. Perceived organizational justice was positively associated with organizational commitment and showed a positive indirect association with performance through commitment. Cyberloafing (measured as frequency of non-work online activity at work) was not significantly associated with commitment or performance in the tested model. Organizational commitment was positively associated with performance and mediated the boredom–performance and justice–performance relationships. Conclusion: The results suggest that, in this setting, commitment is a more reliable pathway linking workplace experience to performance than cyberloafing. Practical implications should be interpreted cautiously given the cross-sectional and self-reported design.